The Forum of Federations Handbook on Local Government in Federal Systems - Steytler, Nico (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This book brings together leading scholars and practitioners from around the globe to examine the current roles of, and future trends in, local government structures and mechanisms in 16 different federal and federal-type countries. In doing so, this volume explores pressing topics such as the institutions of local government, constitutional recognition, local government competencies, financial management, intergovernmental relations, political culture, and the impact of the COVID-19 pandemic on the role of local government in federal systems. Contributors to this volume provide a timely and comprehensive account of the integral role local governments play in federal countries and offer illuminating perspectives on how these roles may change as individual federal systems evolve. These individual analyses are contextualized in a comparative perspective in order to gain a holistic understanding of the challenges and opportunities of various local government dynamics in differentregions around the world. Chapter 16 is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com. Nico Steytler is a professor emeritus at the Dullah Omar Institute of Constitutional Law, Governance and Human Rights of the University of the Western Cape, South Africa.